Predictors for mortality of inpatients of COVID-19 in Mumbai - Dhikale, Prasad T.; Chavhan, Smita S.; Adsul, Balkrishna B.; Kinge, Kirti V.; Gokhale, Chinmay N.; Ingale, Aniket R. (International Journal Of Community Medicine And Public Health, 2021)
Background: The estimation of risk factors for death can help in modifying the screening, treatment strategy and saving valuable lives. The published data about this topic from India is scarce. We aim to explore the risk factors of in-hospital deaths for COVID-19 patients. Methods: This was a hospital-based cross-sectional study. All COVID-19 patients positive on reverse transcriptase–polymerase chain reaction (RTPCR) test who were admitted in this dedicated COVID hospital (DCH) in April to July 2020 and with definite outcome (death or discharge) till end of September 2020 were included in this study. To explore the risk factors associated with in-hospital death univariate and multivariate logistic regression models were used. Results: Of the 6195 patients, 450 (7.26%) died. Age 40-60 years [AOR (CI)=4.53 (2.71-7.58)], age >60 years [AOR (CI)=17.42 (10.55-28.75)], suffering from diabetes mellitus [AOR (CI)=2.08 (1.66-2.6)], cardiovascular diseases [AOR (CI)=1.57 (1.14-2.17)], hypertension [AOR (CI)=1.43 (1.14-1.8)], chronic kidney diseases [AOR (CI)=2.78(2.02-3.82)] were found to be significant predictors of death after adjusting for potential confounders. Conclusions: Age >40 years, diabetes mellitus, cardiovascular diseases, hypertension, chronic kidney diseases are the independent predictors for mortality in COVID-19. These high risk groups should be given special attention for screening and treatment.